Young adolescents' comprehension of literary texts as mediated by the reinterpretation - representation of literary texts through drama : a literary unit on humane and environmental education - Leslie, Laurie Elizabeth (My University, 2003)
This qualitative study describes the relationship between young adolescent readers’ comprehension of environmentally-themed literary texts and the representation and reinterpretation of those texts through drama. The participants in this study were four members of one response group from a Grade 6 class engaged in a five week, text-based unit on humane and environmental education. Three themes emerged from the analysis of the data; curriculum design and implementation, comprehension, and metacognitive awareness. Data analysis was facilitated by Protherough’s (1983) framework for response, Rubin’s (1990) levels of comprehension, and Eisner’s (2003) dimensions of curriculum. Various factors influenced student comprehension during the study. These included; i) elements of design such as the conceptual framework of the unit, the conceptual linking of texts, the guided practice of using strategies to promote comprehension and metacognitive awareness, the use of drama to mediate comprehension, and sustained engagement with related text sets; (ii) planned and spontaneous teacher interventions to scaffold learning experiences and facilitate critical literacy; and, (iii) opportunities for shared and private engagement, response and reflection through oral, written, and dramatic symbolic systems. The detailed design and implementation of the unit on humane and environmental education illuminates the processes undertaken by educators involved in curriculum design, development and implementation. It also provides a comprehensive model for the teaching of humane and environmental education within the conceptual framework of a response-based language arts unit.
Keywords: Reading comprehension (Study and teaching, Elementary); Language arts (Elementary); Drama in education